A preliminary study on productivity investments in tourism security of a multi-islands province: Community perspectives for holiday destination holistic strategy for Community-Based Tourism model of Romblon, the Philippines - Andalecio, Avi Ben P.; Martin, Edwin S. (Journal of Tourism, Culinary, and Entrepreneurship (JTCE), 2022)
Community-Based Tourism is seen for having a huge impact on rural communities in the Philippines and many countries. It is generally known for its pro-poor implications that deliver socio-cultural, ecological, and economic benefits to steer a community if directed with strong policies. CBT has a great potential on elevating the said aspects of a locality for community development. Hence, the proponent attempted to comprehensively determine the perceptions of key actors in CBT with quantitative approaches to shed light on its costs and benefits in the communities of Romblon Province in the Philippines. Structural Equation Modeling (SEM) was utilized as the main research design to impute relationships on latent variables. In the second and final phase of the research project, the proponents will develop a holistic strategy for a provincial CBT model through a thorough review and analysis of public policies in the past 10 years. Data Mining on LGUs and Communities through SEM (survey method), Econometrics (LGU Data Analytics), and Key-Informant Interviews (face-to-face interview) will be the main approaches of the study.